2023
DOI: 10.1177/23259671231214803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Revision ACL Reconstruction Using Iliotibial Band Augmented With Allograft Versus Bone–Patellar Tendon–Bone Autograft With Lateral Extra-articular Tenodesis

Morad Abou Al Ezz,
Antoine Gerometta,
Eugenie Valentin
et al.

Abstract: Background: Bone–patellar tendon–bone (BTB) anterior cruciate ligament reconstruction (ACLR) is one of the conventional techniques in the revision setting especially after a primary hamstring tendon graft. The use of the iliotibial band (ITB) augmented with allograft (AG) is an encouraging graft alternative for ACLR in terms of clinical and biomechanical data in the literature. Purpose: To compare the clinical outcomes of BTB graft with lateral extra-articular tenodesis, modified Lemaire (BTB-LET), and an ITB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The main finding of the present review was that donor age could not be considered to negatively influence the biomechanical properties of the allografts used in ACL reconstruction; although few studies reported a weak correlation of the age with the stress and the tensile strength of donor tissues. Given that, in the context of ACL revisions and, in some cases, even in primary reconstructions, allografts have mostly shown comparable results to autografts [1,2,18], and, based on the existing evidence, there are currently no contraindications to use allografts from donors over 40 years of age in these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main finding of the present review was that donor age could not be considered to negatively influence the biomechanical properties of the allografts used in ACL reconstruction; although few studies reported a weak correlation of the age with the stress and the tensile strength of donor tissues. Given that, in the context of ACL revisions and, in some cases, even in primary reconstructions, allografts have mostly shown comparable results to autografts [1,2,18], and, based on the existing evidence, there are currently no contraindications to use allografts from donors over 40 years of age in these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Since no checklist is present to perform a quality appraisal for biomechanical studies assessing allograft properties, a five-item that regarded the study protocol was assessed, based on the arbitrary decision of the authors of this review. The items assessed were (1) Sample size of at least 50 specimens; (2) adequate setup description (with the description of testing protocol, machine used and graft preparation); (3) donor age role assessed as the primary outcome of the study; (4) consideration of confounding factor in the analysis (e.g., sex, irradiation, height); (5) evaluation of each type of allograft separately. For each item fulfilled, one point was assigned to the study.…”
Section: Data Summary and Quality Assessmentmentioning
confidence: 99%